Equality, Prudence, and Ethical Individualism - Weale, Albert (Journal of Income Distribution®, 2024)
The idea of equality encompasses two logical aspects. First, it names a mathematical relation. Second, it identifies an important ethical value. This article considers the potential connection between these two aspects of equality by examining assumptions about risk aversion on the part of a decision maker operating behind a veil of ignorance. It presents the main theorems found in the work of Peter Lambert and places them within the context of a discussion on how the construction of the veil of ignorance might provide an ethical justification for social and economic equality. Additionally, it introduces the idea of the prudent decision-maker behind the veil of ignorance as one way of explicating the risk averse choices. Finally, it speculates on the extent to which the axiom of separability in rational choice should be required, while also questioning the extent to which the idea of separable social welfare functions exhibits a form of ethical individualism.